A cardiac cause for deafness. (28th October 2013) - Naha, Kushal; Vivek, G; Shetty, Ranjan K; Dias, Lorraine Simone
Abstract : We describe a case of a 49-year-old diabetic man with a history of myocardial infarction, presenting with deafness for 2 weeks. Initial assessment by otorhinolaryngologists was suggestive of sensorineural hearing loss. Subsequently, the cardiac evaluation showed an apical clot in the left ventricle. Careful neurological reassessment and a cranial MRI yielded a diagnosis of cortical deafness with auditory agnosia secondary to bilateral temporal infarcts. Doppler and MRI ruled out carotid artery thrombosis. The temporal infarcts were therefore considered to be cardioembolic in origin. Cardioembolic stroke is an important differential diagnosis for patients presenting with neurological symptoms on a background of cardiac disease.